Preservice Teachers' Self-efficacy During a Field Experience at a Juvenile Detention Facility. (2nd January 2022) - Pytash, Kristine E.; Hylton, Rhonda
ABSTRACT: The purpose of this study was to explore preservice teachers' perceptions of self-efficacy during a field experience at a juvenile detention facility as they taught writing. A mixed-methods study was employed to investigate preservice teachers' perceptions of self-efficacy, their perceptions of students, and their writing instruction. Analysis revealed that self-efficacy scores had statistically significant increases. This data was supported by preservice teachers' perceptions of students and their writing instruction over the course of the field experience.